Expressing the same by the different : the subjunctive vs the indicative in French - Dreer, Igor (Studies in functional and structural linguistics ;, 2007)
This volume offers an alternative, sign-oriented analysis of the distribution of the French Indicative and Subjunctive. It rejects both government and functions, attributed to both moods, and shows that the distribution of the Indicative and the Subjunctive is motivated by their invariant meanings. The volume illustrates the close interaction between the Indicative and the Subjunctive, as linguistic signs, and signs of other grammatical systems, contextually associated with the invariant meanings of both moods. Special consideration is given to the use of the Indicative and the Subjunctive in.